(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Mental health problem is a prevalent disorder in the present age at global level in which the person affected is not able to contribute either to his own benefit or to the society. The students with this problem are not able to concentrate on their studies or take care or their well-being and they are not able to contribute in the national development. The problem if not attended to will result in heavy loss to the economic and social conditions of the nations. The study was targeted on the Muslim as the Muslim community is a community at risk due to poor economic and educational prospects. The nation cannot progress without mainstreaming this important segment of the society. The girls have been selected to form the sample of this study because they are the future mothers and will nurture the society and thus have the capacity to take a nation to great heights. A generation with mentally unhealthy mothers cannot develop to their full potentiality and are also at risk of becoming mentally unhealthy. The comparison has been made between the adolescent girls of U.P. Board schools and CBSE Board schools on six dimensions of mental health. The findings show that on the first three dimensions, i.e., Emotional Stability, Overall Adjustment and Autonomy there was no significant difference between the two samples while U.P. Board girls performed better on fourth and fifth dimensions of Security-Insecurity and Self Concept. The CBSE Board girls performed better on the sixth dimension of Intelligence.